Photocatalytic Microbial Fuel Cells and Performance Applications: A Review - Tong, Yao; Wei, Julong; Mo, Rick; Ma, Hailing; Ai, Fujin (Frontiers in Chemistry, 2022)
In recent years, photocatalytic microbial fuel cells (PMFC) have gradually become a hot research topic in pollutant treatment, using either in situ or indirectly the oxidation of organic pollutants by catalytic materials under light and the biodegradation and mineralization of various components in wastewater by microorganisms, or through the generation of electricity by the microbial fuel cell (MFC) system to promote the photogeneration and separation of electrons and holes by the catalytic materials of the photocatalytic cell (PC) system. This study aims to provide new ideas for the development of environmentally friendly wastewater treatment technologies by investigating the use of photocatalytic cells for the efficient degradation and resource utilization of target pollutants. This study aims to raise awareness of the use of photocatalytic microbial fuel cells for pollutant degradation by providing an overview of the practical status of photocatalytic microbial fuel cells. This is achieved by reviewing the key cathode development, production capacity, and progress in the degradation of pollutants in photocatalytic microbial fuel cells. The issues facing future developments are also discussed in terms of how photocatalytic microbial fuel cells work and how they degrade pollutants. This study shows that photocatalytic microbial fuel cells are beneficial for achieving renewable energy (bioenergy, photovoltaic, etc.) capacity and dealing with environmental pollution and that this is a novel technology that deserves to be promoted to achieve the current dual carbon targets.